2020
DOI: 10.1038/s41419-020-02889-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Hoxaas3 promotes lung fibroblast activation and fibrosis by targeting miR-450b-5p to regulate Runx1

Abstract: Long noncoding RNAs (lncRNAs) participate in organ fibrosis and various pulmonary diseases, but its role in idiopathic pulmonary fibrosis (IPF) is not fully understood. In this study, we found lncRNA Hoxaas3 (Hoxaas3) was up-regulated in the mice model of BLM-induced PF and TGF-β1-induced fibrogenesis in lung fibroblasts (LF). Overexpression of Hoxaas3 promoted fibrogenesis, whereas Hoxaas3 inhibition attenuated lung fibrosis both in vitro and in vivo, through regulation of miR-450b-5p. Furthermore, miR-450b-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…However, to validate the effects of RUNX1 inhibition in vitro we used AI-14-91 a validated RUNX1 inhibitor in the HMEC-Ls. Additionally, we have shown that Ro24-7429 causes a reduction in fibrotic makers, a phenotype also reported in studies that inhibited RUNX1 through molecular approaches ( 3 ). We report that RUNX1 localization and signal is increased in a subset of human lungs infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, to validate the effects of RUNX1 inhibition in vitro we used AI-14-91 a validated RUNX1 inhibitor in the HMEC-Ls. Additionally, we have shown that Ro24-7429 causes a reduction in fibrotic makers, a phenotype also reported in studies that inhibited RUNX1 through molecular approaches ( 3 ). We report that RUNX1 localization and signal is increased in a subset of human lungs infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 78%
“…TGF-β1 activation induces extracellular matrix production, and its effects are mediated through the SMAD2/3 pathway as illustrated through SMAD3 knockout that was found to prevent fibrosis in the bleomycin mouse model ( 42 ). Recent publications have highlighted the role of TGF-β1/SMAD/RUNX1 signaling in IPF ( 3 ). There has been growing interest in the role of RUNX1 inhibition in preventing fibrosis in various organ systems including renal tubular epithelial cells in which RUNX1 was found to regulate markers of EMT and knockout of RUNX1 prevented kidney fibrosis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, RUNX1 modulates the cellular response to TGF-β and promotes myofibroblast differentiation in both marrow-derived and tissue-resident mesenchymal stem cells [ 33 ]. Lin et al [ 34 ] also showed that RUNX1 can promote fibroblast activation and increase α-SMA and fibronectin expression. Additional analysis showed that FER1L4 can induce dysregulation of pathways discovered in TF analysis by acting as ceRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent in ammation creates a microenvironment that promotes adaptive immunity, proliferation and migration of broblast, secretion of extracellular matrix and deposition of collagen, eventually leading to abnormal lung tissue remodeling and obstructive air exchange, even death [14,15]. The broblast to myo broblast transition is the hallmark of brotic diseases, leading to excessive synthesis and deposition of ECM like Collagen, Fibronectin and Elastin [16,17]. Thus, suppression of EMT process, in ammatory cascade response and broblast activation represents a visible approach for the amelioration of pulmonary brosis.…”
Section: Introductionmentioning
confidence: 99%